Analysis of the Effect of Artificial Intelligence Integration in Design Learning on Creativity, Reflection, and Mindset - Nur Indah Pratiwi; Serly Sasmita; Andi Dio Nurul Awalia; Dian Puspita Sari Andri (Indonesian Technology and Education Journal, 2025)
The development of Artificial Intelligence (AI) in education, especially in designteaching, offers great potential to improve students' creativity, reflection, anddesign thinking mindset. This study aims to evaluate the effect of AI integrationin design-based learning on students' creative thinking ability, reflection, anddesign mindset. The study used quantitative methods with a cross-sectionaldesign, involving 82 respondents from various departments in higher educationinstitutions. The research instrument was a questionnaire covering aspects ofcreativity, reflection, and design mindset. The data analysis technique useddescriptive analysis. The results showed that 59.76% of the respondents were 19years old, and most (85.37%) were 3rd semester students. The use of AI in designbasedlearning was proven to increase student creativity with an average score of3.66 on a scale of 5, strengthen reflection skills with an average of 3.63, andimprove design thinking mindset with an average of 3.75. However, the resultsalso revealed that AI is more effective as a supporting tool in the learning processrather than replacing direct interaction between students and educators. Therefore,AI can be integrated as a tool that supports creativity, but still requires the role ofhuman guidance.